Arching of force chains in excavated granular material - Wang, Meimei; Wang, Jin-An; Li, Fei; Liang, Chao; Yang, Liu (Frontiers in Earth Science, 2024)
The physical arch and the arch effect are related to many geotechnical problems, such as the stability of mine openings, a tunnel's shape, and disaster prevention. However, observing the arch in geomaterial is challenging due to Earth's invisible force network distribution. The arch shape is a critical parameter related to the arching effect, which is still an open question. Specifically, the force network evolution after local excavation in granular material is revealed using the photo-elastic technique, and the system pressure variation is calculated qualitatively in particle scale according to the G 2 algorithm. Besides, the force chain arch is formed by strong force chains, which are important in redistributing the stress field. The principal direction of the spatial correlation colormap represents the direction of the strong force chains in the network. Based on this preferred angle between the strong force chain and the horizontal direction, a simplified force chain arch trajectory is iteratively rebuilt. Then, the total force chain distribution is studied considering both G 2 and the total length of strong force chains, with the corresponding results demonstrating a relationship between the changes in these characteristics and the force chain arch formation.